2005
DOI: 10.1111/j.1399-6576.2005.00737.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral state index during anaesthetic induction: a comparative study with propofol or nitrous oxide

Abstract: The Cerebral State Index(trade mark) behaves as other depth of anaesthesia monitors with a progressive decrease during propofol induction but loss of consciousness with N(2)0 results in no change in CSI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 15 publications
2
30
0
Order By: Relevance
“…However, it is important to remember that our recordings were simultaneous pairs and that the potential influence of fentanyl or other factors would be the same for each pair. The reliability of the cerebral state monitor to describe the effects of various anaesthetics has not been well evaluated, however its limitations as to the effects to nitrous oxide has been shown [17], and this is to our knowledge the first clinical study of this monitor.…”
Section: Discussionmentioning
confidence: 97%
“…However, it is important to remember that our recordings were simultaneous pairs and that the potential influence of fentanyl or other factors would be the same for each pair. The reliability of the cerebral state monitor to describe the effects of various anaesthetics has not been well evaluated, however its limitations as to the effects to nitrous oxide has been shown [17], and this is to our knowledge the first clinical study of this monitor.…”
Section: Discussionmentioning
confidence: 97%
“…Steady state nitrous oxide alone causes a slightly increase in the highfrequency and theta range activity of EEG, but it does not alter BIS or create a significant degree of hypnosis [10]. A minimal or total lack of effect of opiates and nitrous oxide has been reported on anesthetic depth monitors [5,11]. Therefore, the effects of nitrous oxide and fentanyl may be negligible on the results of this study.…”
Section: Discussionmentioning
confidence: 86%
“…Due to these different calculation algorithms, these indices may be different during anesthesia. Very few studies on the CSI have been published [4][5][6][7][8][9], and none of these have compared the BIS and CSI in patients receiving propofol-fentanyl-nitrous oxide anesthesia. The aim of the study reported here was, therefore, to compare the BIS and CSM (CSI) during propofol-fentanyl-nitrous oxide anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The four parameters consist of the a-ratio, b-ratio, a-ratio, b-ratio and BS. 85 Similarly to the already described commercial indexes, the range of adequate anaesthesia is designed to be between 40 and 60. Anderson et al 86 reported that CSI correlated well with BIS and showed similar patterns and numerical values in day-surgery anaesthesia without muscle relaxation, however, which monitor is the more dependable remains to be established.…”
Section: Cerebral State Monitormentioning
confidence: 99%